Nursing care of Jewish Patients - Anna Maria Kostka; Sylwia Anna Krzemińska; Sylwia Durlej-Kot; Adriana Milena Borodzicz; Mariusz Chabowski; Dariusz Janczak (Kazimierz Wielki University, 2017)
Everyone has the right to equal treatment irrespective of color, culture, origin or religion. Jewish patients obey many rules. The use of proper diet, adherence to the principles of purity, prayer, performing rituals is very important for them. Medical staff is committed to providing patients with safety, regardless of the differences. Understanding the most important values, ethics and practices of Judaism will help to provide professional care for the patient of Jewish faith. Appropriate communication, understanding and tolerance are essential for creating a relationship with the patient, through which it will be possible to achieve the desired therapeutic effect and improve the quality of life of patients.